contestada

b) The first five terms in a different sequence are -29, -26, -21, -14, -5. Find, in terms of n, a formula for the nth term, V, of the sequence. ​

Respuesta :

If [tex]v_n[/tex] is the n-th term in the sequence, observe that

[tex]v_2 - v_1 = -26 - (-29) = 3[/tex]

[tex]v_3 - v_2 = -21 - (-26) = 5[/tex]

[tex]v_4 - v_3 = -14 - (-21) = 7[/tex]

[tex]v_5 - v_4 = -5 - (-14) = 9[/tex]

and if the pattern continues,

[tex]v_n - v_{n-1} = 2n - 1[/tex]

so the sequence is defined recursively by

[tex]\begin{cases} v_1 = -29 \\ v_n = v_{n-1} + 2n - 1 & \text{for } n > 1 \end{cases}[/tex]

By this definition,

[tex]v_{n-1} = v_{n-2} + 2(n-1) - 1 = v_{n-2} + 2n - 3[/tex]

[tex]v_{n-2} = v_{n-3} + 2(n-2) - 1 = v_{n-3} + 2n - 5[/tex]

and so on. Then by substitution, we have

[tex]v_n = v_{n-1} + 2n - 1[/tex]

[tex]v_n = (v_{n-2} + 2n - 3) + 2n - 1 = v_{n-2} + 2\times2n - (1 + 3)[/tex]

[tex]v_n = (v_{n-3} + 2n-5) + 2\times2n - (1 + 3) = v_{n-3} + 3\times2n - (1 + 3 + 5)[/tex]

and if we keep doing this we'll eventually get [tex]v_n[/tex] in terms of [tex]v_1[/tex] to be

[tex]v_n = v_1 + (n-1)\times2n - (1 + 3 + 5 + \cdots + (2(n-1)-1))[/tex]

Evaluate the sum:

Let

[tex]S = 1 + 3 + 5 + \cdots + (2(n-1)-1) = 1 + 3 + 5 + \cdots + (2n-3)[/tex]

[tex]S' = 2 + 4 + 6 + \cdots + (2n - 2)[/tex]

Then

[tex]S + S' = 1 + 2 + 3 + 4 + \cdots + (2n-3) + (2n-2) = \displaystyle \sum_{k=1}^{2n-2} k[/tex]

Recall that

[tex]\displaystyle \sum_{i=1}^n i = 1 + 2 + 3 + \cdots + n = \dfrac{n(n+1)}2[/tex]

so that

[tex]S + S' = \dfrac{(2n-2)(2n-1)}2[/tex]

and

[tex]S' = 2 + 4 + 6 + \cdots + (2n-2) = 2 \left(1 + 2 + 3+ \cdots + (n-1)\right) = (n-1)n[/tex]

So, we find

[tex]S = (S + S') - S' = \dfrac{(2n-2)(2n-1)}2 - n(n-1) = (n-1)^2[/tex]

Then the n-th term to the sequence is

[tex]v_n = v_1 +2n(n-1) - S = -29 + 2n^2 - 2n - (n-1)^2 = \boxed{n^2-30}[/tex]